Content Validation and Evaluation of an Endovascular Teamwork Assessment Tool. Issue 1 (July 2016) - Hull, L.; Bicknell, C.; Patel, K.; Vyas, R.; Van Herzeele, I.; Sevdalis, N.; Rudarakanchana, N.
Abstract : Objective/Background: To modify, content validate, and evaluate a teamwork assessment tool for use in endovascular surgery. Methods: A multistage, multimethod study was conducted. Stage 1 included expert review and modification of the existing Observational Teamwork Assessment for Surgery (OTAS) tool. Stage 2 included identification of additional exemplar behaviours contributing to effective teamwork and enhanced patient safety in endovascular surgery (using real-time observation, focus groups, and semistructured interviews of multidisciplinary teams). Stage 3 included content validation of exemplar behaviours using expert consensus according to established psychometric recommendations and evaluation of structure, content, feasibility, and usability of the Endovascular Observational Teamwork Assessment Tool (Endo-OTAS) by an expert multidisciplinary panel. Stage 4 included final team expert review of exemplars. Results: OTAS core team behaviours were maintained (communication, coordination, cooperation, leadership team monitoring). Of the 114 OTAS behavioural exemplars, 19 were modified, four removed, and 39 additional endovascular-specific behaviours identified. Content validation of these 153 exemplar behaviours showed that 113/153 (73.9%) reached the predetermined Item-Content Validity Index rating for teamwork and/or patient safety. After expert team review, 140/153 (91.5%) exemplars were deemed to warrant inclusion in the tool. More than 90% of the expert panel agreed that Endo-OTAS is an appropriate teamwork assessment tool with observable behaviours. Some concerns were noted about the time required to conduct observations and provide performance feedback. Conclusion: Endo-OTAS is a novel teamwork assessment tool, with evidence for content validity and relevance to endovascular teams. Endo-OTAS enables systematic objective assessment of the quality of team performance during endovascular procedures.